Ephedrine, pseudoephedrine, and amphetamine prevalence in college hockey players - Bents, R. T.; Tokish, M. J. M.; Goldberg, L. (The Physician and Sportsmedicine, 2004)
BACKGROUND: Performance-enhancing drugs are used by some athletes, even though the substances may be potentially dangerous and some are banned. OBJECTIVE: To assess the use of metabolic stimulants among collegiate hockey players. METHODS: Surveys were administered to college hockey players on five teams. Participation was voluntary, and respondents remained anonymous. The survey included questions regarding use of specific stimulants (eg, ephedrine, amphetamines, pseudoephedrine), awareness of potential side effects, and knowledge of National Collegiate Athletic Association (NCAA) rules. RESULTS: More than half (58%) of the 122 college hockey players who completed the survey reported past or present use of the specific stimulants. Almost half (46%) reported pseudoephedrine use to enhance performance, including 24% who indicated current use, and 38% reported ephedrine use, including 11% who admitted current use. Stimulant users had good knowledge about the potential side effects of ephedrine, including sudden death, hypertension, and insomnia. Nearly all (92%) stimulant users were aware of the current NCAA ban of ephedrine. Over 33% stated they would use a banned substance if it would help them get to the National Hockey League. CONCLUSION: A large number of collegiate hockey players admit to using metabolic stimulants despite knowledge of side effects and the NCAA ban on two of these substances. More effective educational interventions, perhaps coupled with a stronger testing policy, may be necessary to curb this potentially dangerous practice and some are banned.